Landing of Tenualosa ilisha (Hamilton - Buchanan, 1822) from the Iraqi marine waters and the southern part of Shatt Al-Arab at Basrah city, Iraq - younis, Kadhim H.; Jabir, Amir A.; Ahmed, Arafat R.; Hameed, Tark (Iraqi Journal of Aquaculture, 2021)
In the present study, data on total fishing of Tenualosa ilisha have been collected from the Iraqi marine waters and the southern part of Shatt Al-Arab which were landed at Basrah city. The study was conducted during the period from January 2013 to December 2013, from 41 Sampling sites (stations). The total number of landed T. ilisha was 1141671 individuals; the highest numbers of landed T. ilisha were obtained during April and May which were 301598 and 339748 individuals with a percentage of 26.4 % and 29.8 % of the total number of landed fishes, respectively. The total weight of the landed T. ilisha was 560.053 tons and its highest level was obtained during March 81.805 tons, April 151.500 tons, May 169.700 tons, and June 117.900 tons with a percentage of 27.05, 14.6, 30.30, and 21.05 % of the total weight of landed T. ilisha then start to decrease to lowest level in January 300 kg, 0.053 % of the total weight of the landed fish. The numbers of the large sized T. ilisha landed (larger than 24 cm) were 1089896 individuals with a total weight of 545,283. The highest number and weight of the landed fishes at Al-FAO station 185520 individuals, 185.520 tons, and the lowest number and weight was at Al-Behar station was 23686 individuals, 23.686 tons. The total number of fishing trips which were catching T. ilisha during 2013 was 11042 sampling trips. The highest fishing trips were recorded during March (1580), April (1512), May (1670), June (1277), July (1177), and the lowest fishing trips were during December (221 trips).